Constructed Wetland Tipe Horisontal Subsurface Flow Menggunakan Rumput Odot untuk Pengolahan Efluen IPAL Tahu - Irene AA Suwandhi; Novirina Hendrasarie; Dewi Rahyuni (Jurnal Serambi Engineering, 2022)
The effluent of tofu’s anaerobic digester contains organic matter and require further treatment. Constructed wetland (CW) using forage grass plant is one of the alternatives. The study is aimed to observe the effect of CW’s stage variation and planting duration on TSS and COD effluent. Plant growth also observed duringoperation. Two CWs horizontal subsurface tank of dimension 100 cm x 50 cm x 50 cm were arranged in series as stage 1 and 2. Tank was planted with Pennisetum purpureum c.v Mott at spacing of 25 cm, tank without plants as control, and operated at hydraulic loading rate of 0.1 m3/m2.day. Temperature, pH and plant height was measured every 2 days, TSS and COD every 1-2 week. The study showed, there was relatively no temperature difference between control and planted CW. The pH effluent increased with the pH of stage II being higher than stage IThe TSS and COD removal efficiency in planted CW was 61-90 % and 27-85 %, while for control was 8-85 % and 13-79 %, respectively. Plant can grow, indicated by the addition of plant height and plant weight during harvesting. In conclusion, CW stage and planting duration had effect on TSS and COD effluent.